Clinical Efficacy of Endocytoscopy for Gastrointestinal Endoscopy - Masashi Misawa; Shin-ei Kudo; Yuki Takashina; Yoshika Akimoto; Yasuharu Maeda; Yuichi Mori; Toyoki Kudo; Kunihiko Wakamura; Hideyuki Miyachi; Fumio Ishida; Haruhiro Inoue (Korean Society of Gastrointestinal Endoscopy, 2021)
Endocytoscopy (EC) is a contact-type optical endoscope that allows in vivo cellular observation during gastrointestinal endoscopy and is now commercially available not only in Japan but also in Asian, European Union, and Middle Eastern countries. EC helps conduct a highly accurate pathological prediction without biopsy. Initially, EC was reported to be effective for esophageal diseases. Subsequently, its efficacy for stomach and colorectal diseases has been reported. In this narrative review, we searched for clinical studies that investigated the efficacy of EC. EC seems to accurately diagnose gastrointestinal diseases without biopsy. Most of the studies aimed to clarify the relationship between endocytoscopic findings of gastrointestinal neoplasia and pathological diagnosis. Some studies have investigated non-epithelial lesions or diseases, such as inflammatory bowel disease or infectious diseases. However, there are few high-level pieces of evidence, such as randomized trials; thus, further studies are needed.